In vivo gene transfer of endothelial nitric oxide synthase decreases portal pressure in anaesthetised carbon tetrachloride cirrhotic rats. Issue 3 (1st September 2002) - Van de Casteele, M; Omasta, A; Janssens, S; Roskams, T; Desmet, V; Nevens, F; Fevery, J
Abstract : Background: Portal hypertension in cirrhosis results from enhanced intrahepatic resistance to an augmented inflow. The former is partly due to an imbalance between intrahepatic vasoconstriction and vasodilatation. Enhanced endothelin-1 and decreased activity of hepatic constitutive endothelial nitric oxide synthase (NOS 3) was reported in carbon tetrachloride (CCl4 ) cirrhotic rat liver. Aims: To study whether an increase in hepatic NOS 3 could be obtained in the CCl4 cirrhotic rat liver by in vivo cDNA transfer and to investigate a possible effect on portal pressure. Methods: Hepatic NOS 3 immunohistochemistry and western blotting were used to measure the amount of NOS 3 protein. Recombinant adenovirus, carrying cDNA encoding human NOS 3, was injected into the portal vein of CCl4 cirrhotic rats. Cirrhotic controls received carrier buffer, naked adenovirus, or adenovirus carrying the lac Z gene. Results: NOS 3 immunoreactivity and amount of protein (western blotting) were significantly decreased in CCl4 cirrhotic livers. Following cDNA transfer, NOS 3 expression and the amount of protein were partially restored. Portal pressure was 11.4 (1.6) mm Hg in untreated cirrhotic (n=9) and 11.8 (0.6) in lac Z transfected (n=4) cirrhotic rats but was reduced to 7.8 (1.0) mm Hg (n=9) five days after NOS 3 cDNA transfer. No changes were observed in systemic haemodynamics, in liver tests or urinary nitrates, or in NOS 3 expression in lung or kidney, indicating a highly selective transfer. Conclusions: NOS 3 cDNA transfer to cirrhotic rat liver is feasible and the increase in hepatic NOS 3 leads to a marked decrease in portal hypertension without systemic effects. These data indicate a major haemodynamic role of intrahepatic NOS 3 in the pathogenesis of portal hypertension in CCl4 cirrhosis.